Increasing the Competitiveness and Performance of Enterprises Focusing on Innovation Activity – Empirical Survey - Činčalová, Simona (Oeconomica, 2017)
The paper focuses on selected factors increasing the competitiveness and performance. It analyses specific factors, such as human resources, corporate culture, access to customers, quality and cost of production, but especially innovation activity. Innovations in general are an integral part of the activities of each company because of new technologies and new possibilities of solving those situations in this period. Innovations that are correctly applied, can give the companies a competitive advantage through the cost savings and performance improvement.
Zvyšování konkurenceschopnosti a výkonností podniků se zaměřením na inovační aktivitu - empirické šetření
Keywords: Innovations; competitiveness, development; Inovace; konkurenceschopnost; rozvoj